Development of E-Module Assisted by Flip PDF Professional Application Based on Guided Inquiry on Newton's Law Material - Zahara Puspa Ningrum; Lukman Hakim; Sulistiawati Sulistiawati (Jurnal Pembelajaran Fisika, 2023)
This study aims to produce an e-module assisted by a professional flip PDF application based on guided inquiry on Newton's law material that is valid for students to use. The subject used is in class X at Gajah Mada 3 Palembang High School in the even semester of the 2020/2021 academic year. This research is a Research and Development (R&D) study using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. This research is only limited to the development stage due to time constraints and also the purpose of this research is only limited to developing and producing e-modules that are valid and practical. After conducting the research, the overall results were obtained, namely for validity based on material aspects, an average value of 88.8% was obtained in the